Rehabilitation system for upper limb: steering wheel control - Othman, Mohamad Khairul Anuar (2017)
Rehabilitation using haptic interface are more interesting and enjoyable compared to conventional rehabilitation technique because patient can experience real time effect of their movement. This project proposed to design a haptic based rehabilitation system by mimicking real-life scenario in dot moving game controlled via steering wheel and to analyse the performance of the system. Steering wheel mechanism that provide left and right movement turn of about 90° (left) and 90° (right). Steering wheel sensing unit and signal interface unit that allows interactions between the steering wheel mechanism with the LabVIEW software. A Dot Moving Games in LabVIEW used to show real times interaction between the steering wheel mechanism with the LabVIEW. Patient need to maintain the dot on curvy road and avoid from hit side wall or the games will over. Patient progress can be analysed based on their score in the game. The result show there has the difference in the average score based on the ages. The young subject gets higher score compare to the elder subject shows that have the different score between the functional ability based on the ages. It shows that the system performs well and has potential to use as an interaction method of rehabilitation for stoke patient.